Alometria reprodutiva de Podocnemis expansa na Área de Proteção Ambiental Meandros do Rio Araguaia, Goiás, Brasil - Lustosa, Ana Paula Gomes; Alves Junior, José Roberto Ferreira; Silva, Anderson Rodrigo da (Multi-Science Journal, 2017)
não há